Pengaruh Motivasi, Disiplin Kerja, Lingkungan Kerja dan Budaya Organisasi Terhadap Kinerja Pegawai di Dinas Tenaga Kerja dan Transmigrasi Kabupaten Alor - Heri Yanto Namang (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine: the effect of motivation, work discipline, work environment, and organizational culture on the performance of employees at the Department of Manpower and Transmigration of Alor Regency, either partially or simultaneously. The respondents of this study were 35 employees at the Department of Manpower and Transmigration of Alor Regency. Data collection using a questionnaire. The data were then analyzed using the -t test to determine the partial effect and the -F test to determine the simultaneous effect on performance with the results of the study being: 1) The variables of motivation, work discipline, work environment and organizational culture on employee performance have a Pearson product moment correlation value that is above the limit of 0.3 for the validity test. 2) The variables of motivation, work discipline, work environment and organizational culture on employee performance have a Cronbach alpha value above the limit of 0.6 for the reliability test. 3) The variables of motivation, work discipline, work environment and organizational culture on employee performance have a test value for each classic assumption test that is above alpha and passes the classic assumption test. 4) There is an effect of motivation on employee performance as evidenced by the sig t test value of 0.002, which is smaller than the research alpha value of 5% (0.05). 5) There is an influence of work discipline on employee performance as evidenced by the sig t test value of 0.012, which is smaller than the research alpha value of 5% (0.05). 6) There is an influence of the work environment on employee performance as evidenced by the sig t test value of 0.032, which is smaller than the research alpha value of 5% (0.05). 7) There is an influence of organizational culture on employee performance as evidenced by the sig t test value of 0.028 which is smaller than the research alpha value of 5% (0.05). 8) There is an influence of Motivation, Discipline, Work Environment and Organizational Culture on Employee Performance as evidenced by the sig value of the F test which is 0.000 which is smaller than the research alpha value which is 5% (0.05). From the results of the research and the conclusions of the research, the research team suggested to the Respondents (employees of the Alor Regency Manpower and Transmigration Office) that employees are expected to be able to maintain the performance of employees who have been well organized to date, while continuing to improve themselves given the various changes in work situations as happening right now. Suggestions are also given to the Head of the Alor Regency Manpower and Transmigration Service, so that leaders who have nurtured and built the values ​​of work discipline and organizational culture that are well ingrained in this scope of work can be maintained and continue to provide enthusiasm, motivation and innovation for the sake of performance development much better employees and overall job performance. Meanwhile, to determine the effect of the independent variables on the dependent variable, multiple linear regression analysis was used, using the t test to determine the effect partially and the F test to determine the effect simultaneously. Data was collected by distributing questionnaires to employees at the Alor Regency Manpower and Transmigration Office. Data analysis was performed with SPSS tools. Based on the research results, it can be concluded that the variables of motivation, work discipline, work environment, and organizational culture partially and simultaneously have a significant effect on employee performance. This is indicated by the significance value of the t test or partial test on the motivation variable of 0.002 or 0.2%, the significance value of the t test on the work discipline variable is 0.012 or 1.2%, the significance value of the t test on the work environment variable is 0.032 or 3 .2%, the significance value of the t test on organizational culture variables is 0.028 or 2.8% and simultaneously the variables of motivation, work discipline, work environment, and organizational culture together have a significant effect on employee performance at the District Manpower and Transmigration Office Alor. This is indicated by the significance value of the F test of 0.000 or 0.0%.